Production of a bioactive sweetener steviolbioside via specific hydrolyzing ester linkage of stevioside with a β-galactosidase. (1st April 2016) - Chen, Jun-ming; Ding, Li; Sui, Xiao-chen; Xia, Yong-mei; Wan, Hui-da; Lu, Tong
Highlights: The β -galactosidase catalyzes specific hydrolyzing stevioside to steviolbioside. Reaction coupling separation was realized in a packed bed reactor. Steviolbioside inhibits human breast cancer cells as a natural sweetener. Abstract: A β -galactosidase from Kluyveromyces lactis was found to specifically catalyze hydrolysis of the glycosyl ester linkage of stevioside to yield steviolbioside, a rare sweetener that also exists in Stevia rebaudiana leaves. In a packed bed reactor, a reaction coupling separation was realized and a production yield of steviolbioside reached 90% in 6 h. The hydrolysis product steviolbioside presented higher cytoxicity on human normal cells (hepatocytes cell L02 and intestinal epithelial cell T84) than stevioside did. Comparing to the typical chemotherapy agent, 5-fluorouracil (5-FU), steviolbioside presents much lower cytotoxicity on all assayed human normal cells; it presented notable inhibition on human hepatocarcinoma cell Hep3B, human breast cancer cell MDA-MB-231 and human pancreatic cancer cell BxPC-3. The remarkable inhibition on MDA-MB-231 cells makes steviolbioside a potential remedy for human breast cancer, when steviolbioside is served as a natural sweetener.